Further studies in Viola Sect. Melanium (Violaceae). Identity and typification of Viola nana and V. henriquesii, two neglected European Atlantic taxa - Magrini, Sara; Scoppola, Anna (Phytotaxa, 2015)
Based on the analysis of relevant literature and of specimens from European herbaria, Viola nana and V. henriquesii, currently included in V. kitaibeliana, are reaffirmed as independent species. A lectotype is designated here for V. nana from the original material found in the Herbier De Candolle in Genèva Herbarium (G). A lectotype and three syntypes are designated for V. henriquesii from those exsiccata belonging to the gathering cited in the protologue, that were found in the Herbaria of Monaco (M), Stockholm (S), and Meise (BR).